ANALYSIS OF THE EFFECT OF LEADERSHIP AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT UBUD WANA RESORT, GIANYAR - Diary, Ni Luh Putu Devi; Perdanawati, Luh Putu Virra Indah; Adiandari, Ade Maharini; Wijaya, Bagus Arya (ADI Journal on Recent Innovation, 2020)
This study has several objectives. First, to determine the influence of leadership and organizational culture partially on organizational citizenship behavior at Ubud Wana Resort. Second, to find out the influence of leadership and organizational culture partially on job satisfaction at Ubud Wana Resort. Third, to determine the effect of job satisfaction on organizational citizenship behavior at Ubud Wana Resort, and Fourth, to determine the influence of leadership and organizational culture partially on organizational citizenship behavior with job satisfaction as an intervening variable at Ubud Wana Resort. This research is included in causal associative research using a quantitative approach. Quantitative approaches are used because the data used to analyze relationships between variables is expressed by numbers. This study connects the influence of Leadership, Organizational Culture and Job Satisfaction on Organizational Citizenship Behavior. The result of this study are Leadership has a positive and significant effect partially on organizational citizenship behavior, Organizational culture has a positive and significant effect partially on organizational citizenship, Leadership has a positive and significant partial effect on job satisfaction, Organizational culture has a partial and positive influence on job satisfaction, Job satisfaction has a significant influence on organizational citizenship behavior, Leadership influences OCB through Job Satisfaction" is not proven, and Organizational Culture influences OCB through Job Satisfaction" is not proven